BUSINESS ANALYSIS OF NILA FISH (Oreochromis niloticus) ENLARGEMENT IN MUARO SENTAJO VILLAGE SENTAJO RAYA SUB-DISTRICTOF KUANTAN SINGINGI PROVINSI RIAU - Gusta Gusta; Hendrik Hendrik; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research is aboutbusiness analysis Of Nila Fish (Oreochromis Niloticus) Enlargement In Muaro Sentajo Village Sentajo Raya Sub-DistrictOf Kuantan Singingi has been done in 21 Mey- 09 June2018. The purpose of this research is to find out total investment, to find out total production costs, recipients and profits,and to analyze the feasibility of an enlargement cultivation business of Nila Fish in Muaro Sentajo.The research method used is survey method. Determination of respondents was determined by the Purpose Sampling Method. Purposive sampling accordingSugiyono (2010) is a technique of determining samples with special consideration so that they are worthy to be sampled.Based on the results of research Nila Fish enlargement business is the stocking density in each pool with an area of 1.200-2.000 m2 as many as 9.600-16.000 tails / pond and the output in the business of Nila Fish enlargement is the amount of production in each pool as much as 1.516-2.400 kg / pond, the average production costs incurred in the business of Nila Fish enlargement with a pool area of 1.200-2.000 m2 of Rp. 21.966.050,- / harvest to Rp. 36.299.000,- / harvest with a total receipt received of Rp.30.320.000,- /harvest up to Rp. 48.000.000,- / harvest and the amount of profit received was Rp. 8.353.950,- harvest to Rp. 13.806.250,- / harvest and the effort to enlarge Nila Fish in ponds in Muaro Sentajo Village was feasible with RCR value> 1, with FRR value > 6,02% and the value of PPC is between 8,8-912,0 per period or ± 3 years.Keywords: Enlargement Nila Fish, The Business Analysis, Muaro Sentajo